Gesellschaft und Wirtschaft im archaischen Süditalien: Katalog der Gräber: Ein Modell zu Identität und Hexis, ausgehend von Ripacandida und weiteren binnenländischen Gemeinschaften - Heitz, Christian (2021)
The study analyses and reconstructs the social and economic situation of the indigenous inhabitants of southern Italy at the time of the so-called "Greek colonisation" and the selective use of foreign material culture while maintaining an identity that remained largely shaped by indigenous ideas and traditions. It uses the concept of identity, which allows the evaluation of overlapping modes of action and behaviour instead of maintaining a binary opposition between Greeks and 'natives'. In addition, the work discusses in detail for the first time the potential role of mobile pastoralism (transhumance) in the context of archaic southern Italy. Text: http://e-book.fwf.ac.at/o:1553 Katalog der Gräber: http://e-book.fwf.ac.at/o:1554 Fundtafeln: http://e-book.fwf.ac.at/o:1555